Kanak - Parti de libération kanak; Australian National University. Pacific Manuscripts Bureau (Nouméa : Les presses du Kanak, 1976)
No. 1-211 (1976-2006) (incomplete).
Microfilm.
Microfilmed from originals held at: Parti de libération kanak, 2, rue d'Ypres, BO 10003, Nouméa, New Caledonia.
Formed on 28 February 1976, PALIKA (Parti de libération kanak) called for the nationalization of nickel mining, industries and banks. Two PALIKA members were elected to the Territorial Assembly in 1977, including Nidoish Naisseline who represented Mare. PALIKA became a founding member of the Independence Front (Front indépendantiste) in 1979. In 1981, PALIKA moved under the umbrella of the FLNKS (Front de libération nationale de Kanak et socialiste). By 1999, following the Noumea Accord of May 1998, PALIKA had become an established force in New Caledonian politics winning six of the 19 pro-independence seats in the Congress of New Caledonia, and forming the largest block in the northern provincial assemblies. The party continues to be a crucial component of mainstream politics in New Caledonia.
Keywords: Parti de libération kanak -- Periodicals; Kanaka (New Caledonian people) -- Politics and government -- Periodicals; New Caledonia -- Politics and government -- Periodicals